2014
DOI: 10.1111/bph.12681
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species induce MMP12‐dependent degradation of collagen 5 and fibronectin to promote the motility of human umbilical cord‐derived mesenchymal stem cells

Abstract: Background and PurposeReactive oxygen species (ROS) are potent regulators of stem cell behaviour; however, their physiological significance as regards MMP‐mediated regulation of the motility of human umbilical cord blood‐derived mesenchymal stem cells (UCB‐MSCs) has not been characterized. In the present study, we investigated the role of hydrogen peroxide (H2O2) and associated signalling pathways in promoting UCB‐MSCs motility.Experimental ApproachThe regulatory effects of H2O2 on the activation of PKC, MAPKs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 68 publications
1
18
1
Order By: Relevance
“…In the present study, we found that AA uniquely increases the level of MT3-MMP among all the isoforms of MMP to regulate ECM degradation. In contrast to our previous reports showing that secretory MMP-12 participates in the mobilization of hUCB-MSCs in response to some microenvironmental factors, 14 , 29 we identified that AA exclusively upregulates MT3-MMP through Sp1 in promoting the motility of hUCB-MSCs. This implies that the activation of MMPs is distinctively regulated by microenvironmental factors that affect the transcription of many MMP isotypes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that AA uniquely increases the level of MT3-MMP among all the isoforms of MMP to regulate ECM degradation. In contrast to our previous reports showing that secretory MMP-12 participates in the mobilization of hUCB-MSCs in response to some microenvironmental factors, 14 , 29 we identified that AA exclusively upregulates MT3-MMP through Sp1 in promoting the motility of hUCB-MSCs. This implies that the activation of MMPs is distinctively regulated by microenvironmental factors that affect the transcription of many MMP isotypes.…”
Section: Discussioncontrasting
confidence: 99%
“…As Sp1 is responsible for the transcription of many MMP isotypes, which are crucial for cell migration, 28 mRNA levels of MMP s were analyzed with real-time PCR. Among MMP isotypes expressed in hUCB-MSCs, 29 AA distinctively increased the mRNA levels of MMP-12 and MT3-MMP , and decreased MMP-11 and MT1-MMP ( Figure 6a ). AA also increased the protein expression of MT3-MMP, but did not alter the protein level of MMP-12 ( Figure 6b ).…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 , an important factor that leads to oxidative stress‐induced premature senescence (OSIPS), has been demonstrated to inhibit MSC proliferation in a concentration‐dependent manner . H 2 O 2 enhances the release of NF‐κB and β ‐catenin as well as the motility of MSCs by enhancing degradation of collagen 5 and fibronectin and further facilitates osteogenic differentiation of MSCs via up‐regulation of NFE2L2 expression . After treatment with 200 μm H 2 O 2 for 3 to 4 passages, wharton's Jelly derived MSCs become morphologically heterogeneous and irregularly flattened, with significantly up‐regulated expression of senescence markers, including SA‐ β ‐galactosidase, p53, p21, p16 and lysosomal β ‐galactosidase .…”
Section: Antioxidative Capacities Of Senescent and Apoptotic Mscsmentioning
confidence: 99%
“…Alternatively, decellularized ECM from MSCs has been shown to promote the resistance against oxidative stress through the secretion of endogenous antioxidants such as SOD2 [ 122 ]. It has been demonstrated that ECM proteins are the targets of ROS through the activation of MMPs, which can affect MSC motility [ 123 ].…”
Section: Modulation Of Ros Generation Through Stem Cell Microenvirmentioning
confidence: 99%